POLA PERAWATAN GIGI DENGAN KELAINAN PULPA DI RUMAH SAKIT - Zahara Meilawaty; Hestieyonini Hadnyawati; Kiswaluyo K (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2013)
SKRT 1995 showed that 63% of Indonesia people got active dental caries or tooth decay that had been in treatment. Patients usually come to dental clinic is in severe condition and with pulp inflammation. The treatment is endodontic intacanal. Otherwise, not all of hospitals give recommendation for patient to take this treatment. The aim of this study was to know services/ treatment pattern that given by hospital. This was descriptive study that did in Balung, Genteng, and Kalisat hospital. This study used secondary data such as patients visiting data for knowing kind of service that given by dentists. The result showed Balung hospital gave endodontic treatment, but the others didn’t give it.